중국 해상민병대의 국제법적 지위와 효과적 대응방안에 관한 연구 - 이상회; 장유락; 이윤철 (한국해양경찰학회보, 11(2), 2021)
이 연구의 목적은 중국 정부가 운용하는 해상민병대 선박의 국제법적 지위를 명확히 하고, 이에 근거하여 적법하고 효과적인 대응 방안을 강구함에 있다. 중국 정부는 남중국해, 동중국해에서의 해양영역 분쟁에 있어 해상민병대를 적극 활용하고 있는데, 그 활동 영역은 건설, 보급 지원활동을 넘어 직·간접적인 무력위협이나 무력사 용에까지 이르고 있다. 이는 군대를 동원함으로써 갈등 상황이 전쟁으로 격화되는 것을 막으면서도 해양 영역 확대라는 정치적 목적을 달성하기 위한 회색지대 전략의 일환으로 평가된다. 중국과 분쟁 중인 국가들은 해상민병대의 모호한 성격으로 말미 암아 효과적으로 대처하지 못하고 있는데, 이 문제를 해결하는 출발점은 해상민병대 선박의 국제법적 지위를 확정하는 것이며, 이는 곧 적법하고 적절한 대응 모색에 필요 불가결한 선결조건이 된다. 이에 본 연구에서는 국제해양법 규정의 문리적, 의도주의적 해석을 통하여 해상민 병대 선박이 군함의 지위를 가지며, 따라서 해상민병대의 무력사용이나 무력위협 행위는 곧 피침해국가의 적법한 자위권 행사 요건을 구성함을 밝히겠다. 나아가 해상 민병대 선박의 법적 지위를 대외적으로 공개적이고 지속적으로 표명하는 것이 중국의 회색지대 전략을 근본적으로 무력화시키는데 일조함을 제언한다. The purpose of this study is to clarify the international legal status of maritime militia ships operated by the Chinese government and to devise legitimate and effective countermeasures. The Chinese government is actively using maritime militias in maritime disputes in the South&East China Sea, and its activities extend beyond construction or support activities to direct and indirect use of forces. This is evaluated as part of a Gray Zone strategy to achieve the political goal to expanding the maritime territory while preventing the conflict from intensifying into war. Countries in dispute with China have not been able to effectively cope with the ambiguity of the maritime militia, and the starting point for solving this problem would be defining the legal status of the maritime militia ship, which is an indispensable prerequisite for seeking a appropriate response. In this study, through the literary and intentional interpretation of international law of the sea, it would be revealed that the maritime militia ship has the status of a warship, and the use of force or threat by the maritime militia constitutes the requirements for the legitimate exercise of the self-defense. Furthermore, it is suggested that publicly expressing the legal status of maritime militia ships to the World society would contribute to neutralizing China's Gray-Zone strategy fundamentally. KCI Citation Count: 0